Step-by-step explanation:
♤ 3(b-5) = 27
=> 3b - 15 = 27
=> 3b = 27 + 15 = 42
=> b = 42/3
=> <em><u>b</u></em><em><u> </u></em><em><u>=</u></em><em><u> </u></em><em><u>14</u></em><em><u> </u></em><em><u>(</u></em><em><u>Ans</u></em><em><u>)</u></em><em><u> </u></em>
♤ 2x/3 = 6
=> 2x = 6 × 3 = 18
=> x = 18/2
=> <em><u>x</u></em><em><u> </u></em><em><u>=</u></em><em><u> </u></em><em><u>9</u></em><em><u> </u></em><em><u>(</u></em><em><u>Ans</u></em><em><u>)</u></em><em><u> </u></em>
♤ 2(n + 5) = 15
=> 2n + 10 = 15
=> 2n = 15 - 10 = 5
=> n = 5/2
=> <em><u>n</u></em><em><u> </u></em><em><u>=</u></em><em><u> </u></em><em><u>2</u></em><em><u>.</u></em><em><u>5</u></em><em><u> </u></em><em><u>(</u></em><em><u>Ans</u></em><em><u>)</u></em>
♤ a + a + a + a = 24
=> 4a = 24
=> a = 24/4
=> <em><u>a</u></em><em><u> </u></em><em><u>=</u></em><em><u> </u></em><em><u>6</u></em><em><u> </u></em><em><u>(</u></em><em><u>Ans</u></em><em><u>)</u></em>
♤ 4c + 6 = 18
=> 4c = 18 - 6 = 12
=> c = 12/4
=> <em><u>c</u></em><em><u> </u></em><em><u>=</u></em><em><u> </u></em><em><u>3</u></em><em><u> </u></em><em><u>(</u></em><em><u>Ans</u></em><em><u>)</u></em>